Case study and comparison of embodied carbon and construction cost by adopting alternative timber-based hybrid structure system - Ciao-Ning Hsieh; Truong N.M Chau; Si-Jie Syu; Cheng-Chieh Hsu; Meng-Ting Tsai (Tạp chí Khoa học và Công nghệ)
The rise in global temperatures, driven by carbon dioxide emissions, has spurred the construction industry to seek carbon reduction strategies. This study evaluates the environmental benefits of using wood materials in construction by redesigning an existing reinforced concrete (RC) residential building in New Taipei City, Taiwan. Four structural combinations were developed, replacing concrete with timber and steel. Numerical simulations confirmed the feasibility of these systems, and comparisons of embodied carbon, costs, and construction periods were conducted. The proposed hybrid models, which extensively replace concrete with timber and steel for the core, reduced initial embodied carbon by 25.6% compared to the original RC building, though costs increased by 3.9 times. These findings underscore the potential of hybrid timber systems as a sustainable alternative in construction, offering significant carbon reduction benefits for Taiwan while aligning with environmental goals.